Adsorption Efficiency of Crystal Violet Onto Green House Gas Emitting Agro-Waste Obtained from Areca Husk Carbon - Basker, A.; Syed Shabudeen, P.S.; Shekhar, A.P. (Asian Journal of Chemistry, 2014)
An activated carbon produced from agricultural waste was utilized for the adsorption studies of crystal violet from its aqueous solutions. Batch experiments were carried out for the adsorption of dye molecules onto areca husk carbon at room temperature. The factors affecting the rate processes involved in the removal of dye for particle size, adsorbent dosage, initial dye concentration, contact time, pH and temperature have been studied. Pseudo-first order, pseudo-second order kinetics and intra particle diffusion models were attempted to examine the feasibility of the experimental data based upon different initial concentrations. The observed kinetics studies show that the adsorption followed pseudo-first order reaction. The high correlation coefficient of intra particle diffusion model proves the pore diffusion plays an effective role for the adsorption of crystal violet onto areca husk carbon. This adsorption isotherm data was in agreement with the Langmuir, Freundlich and Temkin adsorption isotherm models. Thermodynamic parameters have also been evaluated. The structural and morphological of activated carbon were characterized by FTIR and SEM studies respectively. Main and interaction effects were analyzed by analysis of variance (ANOVA), F-test and p-values to define most important process variables affecting the dye adsorption.